Joint fitting reveals hidden interactions in tumor growth. (21st January 2015) - Barberis, L.; Pasquale, M.A.; Condat, C.A.
Abstract: Tumor growth is often the result of the simultaneous development of two or more cancer cell populations. Crucial to the system evolution are the interactions between these populations. To obtain information about these interactions we apply the recently developed vector universality (VUN) formalism to various instances of competition between tumor populations. The formalism allows us (a) to quantify the growth mechanisms of a HeLa cell colony, describing the phenotype switching responsible for its fast expansion, (b) to reliably reconstruct the evolution of the necrotic and viable fractions in both in vitro and in vivo tumors using data for the time dependences of the total masses alone, and (c) to show how the shedding of cells leading to subspheroid formation is beneficial to both the spheroid and subspheroid populations, suggesting that shedding is a strong positive influence on cancer dissemination. Abstract : Highlights: Mixed cancer cell growing populations are described by the VUN fitting method. The nature of the interaction among some phenotypes is unveiled. HeLa cell colonies show a phenotype switching responsible for their fast expansion. Tumor spheroids reveal the negative effect of the necrotic core on living cells. Shedding cells can be a profitable mechanism for spheroid growth.